Pembelajaran Pendidikan Jasmani Berbasis Pendidikan Karakter Dimasa Pandemi Covid 19 - Suastika Nurafiati; Haeril Haeril; Rabiah AL Adawiyah (Gerak: Journal of Physical Education, Sports, and Health, 2022)
Education directs the process of humanizing humans. With education, it is hoped that people with character and knowledge can be achieved. During the COVID-19 pandemic, national education underwent changes in its implementation. Learning is done by Distance Learning (PJJ). The implementation of physical education based on character education during the COVID-19 pandemic is carried out online. The purpose of this study was to describe learning physical education based on character education during the COVID-19 pandemic at SDN Bontoa Makassar. This research is a qualitative research in which the data obtained from interviews, observations and documentation. The results showed that physical education learning based on character education during the COVID-19 pandemic was carried out online. The implementation of character education-based physical education learning is carried out by integrating the character values of discipline, honesty, hard work and responsibility in every learning planning activity, learning implementation and learning evaluation. The integration of character values in physical education learning activities during the COVID-19 pandemic was carried out by providing examples of exemplary and habituation in attitude.